2019
DOI: 10.1136/bmjopen-2018-021535
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing practice of pregabalin/gabapentin in pain therapy: an evaluation of German claim data

Abstract: ObjectivesTo analyse the prevalence and incidence of pregabalin and gabapentin (P/G) prescriptions, typical therapeutic uses of P/G with special attention to pain-related diagnoses and discontinuation rates.DesignSecondary data analysis.SettingPrimary and secondary care in Germany.ParticipantsFour million patients in the years 2009–2015 (anonymous health insurance data).InterventionNone.Primary and secondary outcome measuresP/G prescribing rates, P/G prescribing rates associated with pain therapy, analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…Following the PBS subsidy of pregabalin, we observed high rates of pregabalin initiation from 2013/14 to 2016/17 with only a slight drop in 2017/18. However, consistent with other studies, 7,17,18 we observed high rates of discontinuation which have been increasing over time, suggesting suboptimal efficacy or low tolerability of pregabalin for the conditions for which it is being used. The lower discontinuation rates in people that initiated on the higher capsule strengths may indicate a better risk–benefit profile, use for different indications, or use in different populations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Following the PBS subsidy of pregabalin, we observed high rates of pregabalin initiation from 2013/14 to 2016/17 with only a slight drop in 2017/18. However, consistent with other studies, 7,17,18 we observed high rates of discontinuation which have been increasing over time, suggesting suboptimal efficacy or low tolerability of pregabalin for the conditions for which it is being used. The lower discontinuation rates in people that initiated on the higher capsule strengths may indicate a better risk–benefit profile, use for different indications, or use in different populations.…”
Section: Discussionsupporting
confidence: 90%
“…Pregabalin use is on the rise globally, 2–4 with growing concerns about off‐label use and misuse 5,6 . Many people initiating pregabalin do not have a diagnosis for an approved indication and there is suspicion that pregabalin is being prescribed for non‐neuropathic pain, particularly low back pain, despite evidence that it is ineffective for this condition 2,3,7 …”
Section: Introductionmentioning
confidence: 99%
“…(5) There are concerns it is being over-prescribed, (2,6) with several studies finding high rates of offlabel use, particularly for non-neuropathic pain conditions where evidence of benefit is unclear. (2,3,7) Pregabalin has abuse potential, and is commonly misused in people with a history of substance use disorder or psychiatric problems. (8)(9)(10) When pregabalin is taken in combination with other medicines with sedative properties, particularly opioids and benzodiazepines, it can lead to central nervous system depression, with the greatest risk observed with high doses.…”
Section: Introductionmentioning
confidence: 99%
“… 5 There are concerns it is being overprescribed, 2 , 6 with several studies finding high rates of off-label use, particularly for non-neuropathic pain conditions where evidence of benefit is unclear. 2 , 3 , 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation